Political Messages On Social Media And Gen Z's Choice In The 2024 Presidential Election: (Phenomenological Study of Gen Z In Jakarta) - Masduki, Damayanti; Widianingsih, Yuliani; Simanihuruk, Hermina (Doctoral Program of Social Science Pasundan University, 2024)
According to the KPU, Gen Z first-time voters contributed 46,800,161 votes or 22.85% of the total number of voters in the 2024 Election. This figure has a significant influence on the success of the Presidential and Vice-Presidential Candidates in gaining votes. Voters who are voting for the first time in the 2024 Presidential Election are an experience that is greeted with enthusiasm and also confusion. Related to this enthusiasm, Presidential and Vice-Presidential Candidates must understand the psychology and motivations of these voters, which will later provide insight to Gen Z in actualizing their enthusiasm in their participation in the political arena. Gen Z voters tend to support candidates who prioritize attention to their interests such as values??on issues such as environmental protection, social justice, and an emphasis on sustainability and ethical considerations that extend to political preferences. Gen Z is known for their mastery of technology, so the process of searching for information is often done through the use of gadgets. However, to embrace Gen Z voters, there is a challenge because Gen Z is wisely involved in the election process by considering the candidate's platform and policies before voting. The purpose of this study is to describe the experiences of Gen Z in Jakarta in carrying out their roles as first-time voters in the 2024 Presidential Election. This study uses a qualitative method with a phenomenological approach. The informants who were interviewed in depth consisted of 10 people who lived in Jakarta. The results of the study show that informants tend to have motivation to use their voting rights, although there are Gen Z who participate at the encouragement of their parents. Gen Z's expectations of leaders are that they can answer problems during previous leadership, have responsibility, track records, experience and vision and mission that can be trusted, and have the soul of a leader. Sources of information accessed are Twitter, television, and parents. The message that sticks is a more specific message that is in accordance with the interests of Gen Z who have a character that is closely related to technology